Multicultural Education Practices at Religiously-Based Schools in Malang - Ibnu Mujib (Al-Albab, 2016)
This study began with an assumption that multicultural education model is practiced in schools in a very limited scope. Therefore, through the subject of PPKN (Civics Education) in schools, multicultural education can be developed. In addition, the school as a laboratory of diversity at the scope of educational institutions is an important medium in the discourse of multicultural education. As a conceptual formulation that was built through the 2013curriculum, the instructional model of Civics education-based on multiculturalism was found to be able to stimulate students’ character building in a more effective, quick and strategic manner. The school, in addition to being an important laboratory of diversity, should also provide multicultural instruction in Civics education with the materials that aid the vision of Civics education instruction with a content of multicultural education in a productive, creative, innovative, and affective way as well as having an effect on the students so as to contribute to the social, civic life and more importantly to the process of building the character and attitude of tolerance among students in schools. Through multicultural education in schools, students learn to accept and understand the cultural differences that affect the differences in usage (how people behave); folkways (habits in the community), mores (code of conduct in the community), and customs (tradition of a community). With multicultural education, learners will be able to accept differences, criticism, and have a sense of empathy, tolerance for others regardless of class, status, gender, ehnic, religion and academic skills.